Developing Islamic Character and Understanding of the Islamic Religion Through the MABIT-Based Pondok Syawal Activity Program - Aji Saputra, Mochammad Ronaldy; Ali, Mukti; Wahyuni, Ekowati (Kariman: Jurnal Pendidikan Keislaman, 2025)
This research aims to analyze the Pondok Syawal activity program based on Malam Bina Iman dan Taqwa (MABIT) in cultivating Islamic character and understanding of the Islamic religion in students at MAN 2 Malang City. This activity program was carried out at the Al-Hayatul Islamiyah Islamic Boarding School, Malang City. This research uses a mixed method (quantitative-qualitative) sequential exploratory design. Data collection was carried out through surveys, in-depth interviews, and participant observation. The research subjects were students at MAN 2 Malang City who took part in the Pondok Syawal program in 1445 H, totaling 20 participants. The research results show that program is effective in cultivating Islamic character and understanding of the Islamic religion in students. This program contributed to the Islamic character of 92.8% (very good) and understanding of the Islamic religion of 78.4% (good). This program provides meaningful and contextual learning experiences for students, so they can understand and practice Islamic teachings better. Then students become more disciplined, have good morals, and understand Islamic teachings better. The findings of this research provide important implications for the implementation of Islamic education programs in madrasas. The MABIT-based Pondok Syawal program can be an alternative Islamic education program that is effective and beneficial for students.